HISTOLOGICAL STUDY ON INTERNAL ORGANS DEVELOPMENT OF MANGROVE SNAPPER, Lutjanus argentimaculatus LARVAE - Ketut Mahardika; Indah Mastuti; Regina Melianawati; Zafran Zafran (Indonesian Aquaculture Journal, 2012)
Mangrove snapper, Lutjanus argentimaculatus is one of highly economic value of marine fish commodity. Culture of this species has been developed a few years ago. Basic data on biological aspect is still limited whereas those kinds of information are needed. Histological study to determine development of internal organs of the larvae of mangrove snapper was conducted. Amount of 15-20 larvae each from 1 day after DAH hatching (1 DAH) up to 30 days after hatching (30 DAH) were collected, fixed in Bouin’s solution for 4-6 hours and then transferred into 70% alcohol. The samples were then embedded in paraffin wax and the sections were stained with haematoxylineosin (H&E). Results showed that the eye retina of the mangrove snapper larvae well developed on 3 DAH, whereas their digestive tract was on 5 DAH. Under this condition, the larvae started feeding as showed by present of natural food tissues in the intestine. Development of digestive tract and other internal organs reached their complete form like in adult fish after 20 DAH.